Physical Condition Analysis of Central Java PPLP Rowing Athletes - Saputro, Ferdian Aji; Wiyanto, Agus; Ratimiasih, Yulia (Journal of Sport Science and Fitness, 2025)
Introduction: The importance of physical condition in rowing is very influential in the development of an athlete. One of the efforts made to improve the physical condition of athletes is to analyze their physical condition, which will be the solution to the problem. Objectives: This study aims to determine the physical condition of rowing athletes at the Central Java Student Education and Training Center (PPLP). Method: This type of research is descriptive quantitative. The population of this study was 10 PPLP Central Java rowing athletes, consisting of 3 boys and 7 girls. The data collection technique of this study used tests and measurements of physical conditions.  The data analysis technique used is descriptive statistics. Result: The results of this study indicate that the physical condition of PPLP rowing athletes in Central Java is quite good in the parameters of flexibility, balance, muscle power, strength, cardiovascular endurance, speed, body composition, and explosive strength. Conclusion: The conclusion of this study is that the physical condition of PPLP rowing athletes is quite good, and there are several aspects that need to be improved, such as cardiopulmonary endurance and flexibility.